Do the roles of dedication, constraint, and temptation-based mechanisms on customer loyalty vary for different length of relationship? - Chuah, Stephanie Hui-Wen; Rauschnabel, Philipp A.; Thurasamy, Ramayah (2017)
Achieving customer loyalty is a primary marketing goal, but cultivating loyalty and reaping its benefits remain ongoing challenges. Building on social exchange theory (SET) and the dedicationconstraint model, this study proposed a novel dedication-constraint-temptation model (DCTM) of customer loyalty by taking into account the boundary condition of relationship length. The DCTM highlights the prominent role of brand equity, switching barriers and alternative attractiveness, as well as their interplay in the formation of customer loyalty. Specifically, the DCTM underlines the important but underexplored role of alternative attractiveness as a mediator, and integrates both established and new antecedents to brand equity and switching barriers. The model was tested using data from an online survey of 331 postpaid mobile users in Malaysia. Partial least square structural equation modeling (PLS-SEM) was used to analyze the data. The results show that customer value anticipation and customer satisfaction are the key antecedents of brand equity (the dedication-based mechanism) for both shorter- and longer-term relationships. However, the effect of customizationpersonalization control only exists for longer-term relationships. In both samples, brand equity exerts a significant influence on customer loyalty, with alternative attractiveness (the temptation-based mechanism) serving as a mediator. The results also reveal that procedural switching costs are the most salient antecedent of switching barriers (the constraint-based mechanism) for both shorter- and longerterm relationships. In contrast, the effect of monetary switching costs only exists for shorter-term relationships, whereas the effect of material benefits loss only exists for longer-term relationships. In either case, the effect of social relationship loss is not significant. Switching barriers, in turn, influence customer loyalty (via alternative alternativeness) and this effect only happens in longer-term relationships. Furthermore, the results from multigroup analysis indicate a significant difference in the effect of switching barriers on alternative attractiveness between shorter- and longer-term customers. Overall, the findings show that shorter-term customers rely on brand equity, whereas longer-term customers depend more on switching barriers and less on brand equity, in forming their loyalty. Based on these findings, we outline how mangers of mobile communications companies should adapt their retention efforts to different relationship types.